2020
DOI: 10.1021/acs.organomet.0c00218
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective C–F Bond Activation/C–C Bond Formation between Fluoropyridines and Cyclopropyl Groups at Zirconium

Abstract: This paper addresses the problem of the strong and inert C−F bond activation of various fluoropyridines by zirconocene derivatives. Dicyclopropylzirconocene, [Cp 2 Zr(c-C 3 H 5 ) 2 ], thermally eliminates cyclopropane, giving the transient intermediate zirconabicyclobutane [Cp 2 Zr(η 2 -c-C 3 H 4 )] that cleaves a C−F bond of pentafluoropyridine selectively at position 2, forming new Zr−F and C−C bonds stereoselectively to give [Cp 2 ZrF{c-cis-CHCH 2 CH(2-NC 5 F 4 )}]. DFT computations indicate the selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Work by Chambers et al has reported one of the most comprehensive studies with C -nucleophile addition-substitutions using PFP demonstrating, in some cases, unique substitution patterns not otherwise observed with O -, S -, and N -nucleophiles . This work was further supported with studies reporting C -nucleophile additions using cyclopropane anion salts of Mg that showed exclusive regioselective addition to the 4-position of PFP while Zn­( c -C 3 H 5 ) 2 and Li­( c -C 3 H 5 ) afforded a distribution of 2- or 4-substituted PFP . In addition, Li­( c -C 3 H 5 ) also produced 2,4-substituted PFP on the heterofluoroaromatic ring limiting substrate diversity with C -nucelophiles.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Work by Chambers et al has reported one of the most comprehensive studies with C -nucleophile addition-substitutions using PFP demonstrating, in some cases, unique substitution patterns not otherwise observed with O -, S -, and N -nucleophiles . This work was further supported with studies reporting C -nucleophile additions using cyclopropane anion salts of Mg that showed exclusive regioselective addition to the 4-position of PFP while Zn­( c -C 3 H 5 ) 2 and Li­( c -C 3 H 5 ) afforded a distribution of 2- or 4-substituted PFP . In addition, Li­( c -C 3 H 5 ) also produced 2,4-substituted PFP on the heterofluoroaromatic ring limiting substrate diversity with C -nucelophiles.…”
Section: Introductionmentioning
confidence: 66%
“…M p maxima at 125 and 130 °C. m/z (% relative intensity) 580 ([M] + , 100), 500 (15), 420 (15), 339 (15), 319 (15), 238 (20), 207 (15).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations